Women's buying behaviour towards organic food - Yeo, Sing Ee (Universiti Malaysia Sarawak (UNIMAS), 2014)
This paper focuses on women and their buying behaviour towards organic food. This paper adopted Theory of Planned Behaviour, a model from Ajzen (1991). This model includes three elements and they are attitude toward behaviour, subjective norm and perceived behavioural control. Relevant literature has been incorporated and thus, it provides a better view and understanding on women's buying behaviour towards organic food. In addition, there is a discussion on purchase intention towards organic food with variables like attitude, subjective norm and perceived behavioural control. This paper also discusses about customer satisfaction and loyalty.